2012
DOI: 10.1590/s1516-635x2012000100002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of breeder age on eggshell thickness, surface temperature, hatchability and chick weigh

Abstract: Two experiments were carried out to study the effect of breeder age on incubation parameters (hatchability, eggshell thickness, egg surface temperature and chick weight). In Exp. 1, fertile eggs (30-and 60-wk-old breeders) were incubated at three different temperatures (36.8, 37.8 and 38.8 o C). Eggshell surface temperature was measured by attaching a thermocouple to the shell and data were collected in a datalogger every ten minutes. This study was conducted according to a 3 x 2 factorial design (three temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
3
20
0
3
Order By: Relevance
“…Furthermore, the eggshell thickness was different in each eggshell region, i.e., it was greatest at the narrow end, followed by the the equator and the large end, thus showing that the region of the air chamber presents the smallest thickness, which facilitates the exit of chick from the egg. These results are concordant with those of Barbosa et al (2012), Morita et al (2010), and Gualhanone et al (2012), who studied the shell thickness of recently hatched eggs from broiler breeders of different ages.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the eggshell thickness was different in each eggshell region, i.e., it was greatest at the narrow end, followed by the the equator and the large end, thus showing that the region of the air chamber presents the smallest thickness, which facilitates the exit of chick from the egg. These results are concordant with those of Barbosa et al (2012), Morita et al (2010), and Gualhanone et al (2012), who studied the shell thickness of recently hatched eggs from broiler breeders of different ages.…”
Section: Discussionsupporting
confidence: 89%
“…Considering that eggshell thickness was measured after the incubation process, the correlation between thickness and conductance may have been impaired. According to Gualhanone et al (2012), eggshell thickness may diminish by around 12.5% between the start of egg incubation and the day of hatching, with variations in this decrease in thickness among the different regions of the eggshell.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha reportado que la cáscara generalmente adelgaza con la edad (17) y que las gallinas jóvenes tienden a producir huevos con cáscara más gruesa que las gallinas viejas (18). Aunque no se midió la calidad de la cáscara en este estudio, si fue evidente que los huevos de las gallinas de 64 semanas se fracturaban más fácilmente, tuvieron el mayor porcentaje de huevos fisurados aunque sin diferencias con las otras edades, y también la cáscara era en general más delgada y con imperfecciones del color y la textura.…”
Section: Discussionunclassified
“…La incubabilidad generalmente es máxima en la porción media de la etapa productiva cuando el It was reported that the shell generally gets thiner with age (17) and that young hens tend to produce eggs with a thicker shell compared to the older ones (18). Although the quality of the shell was not measured in this study, it was evident that those eggs from the 64 weeks old broke or fractured easier, they had the higher percentage of cracked shells although with no differences between the other ages, and also the shell was thiner and with imperfections regarding color and texture.…”
Section: Discussionmentioning
confidence: 99%
“…These structures within the pore canal were seen in samples before incubation, so we considered that they were a feature of goose species and related to the strength of the eggshell and they were not related to the incubation period. Bönner et al [26] reported that the thickness of average of goose eggshell was 530 µm, Gualhanone et al [27] stated that the thickness of average of chicken eggshell was 370 µm and Yamak et al [28] informed that the thickness of average of chicken eggshell was 380 µm. In this study, there was a big difference between the thickness of average of goose eggshells and that of chicken so we compared the thickness of an BİNGÖL, DEPREM, KARADAĞ SARI KORAL TAŞÇI, ASLAN average eggshell statistically among the groups within each species.…”
Section: Discussionmentioning
confidence: 99%